Cloud path, journey of a wandering monk - Muenzen, Paul
Follows Hyongak (Paul Muenzen), an American-born Zen monk and student of Korean Zen master Seung Sahn, on a traditional pilgrimage through South Korea. Cloud Path, Journey of a Wandering Monk is a documentary about a distinguished Buddhist monk. This was originally a locally produced TV program that had been aired in Korea and was selected by the Korea Foundation as an outstanding work for introducing Korean culture abroad. The original content has been dubbed into English, French, and Spanish. The documentary records the activities of Paul Muenzen (Buddhist name: Hyongak), a Harvard University graduate who became a monk, as he learns the Manhaeng, experiences of the secular world. Along with its highly acclaimed cinematography, various aspects of Korea's rich traditional culture, such as samulnori and onggi (crockery), are seen through the eyes of this American monk